Isolasi dan Seleksi Bakteri Endofit untuk Pengendalian Penyakit Darah pada Tanaman Pisang - Husda Marwan; Meity S. Sinaga; . Giyanto; Abdjad Asih Nawangsih (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
Blood disease is one of the important diseases of banana in Indonesia. Endophytic bacteria have potencies as candidates of biocontrol agents to blood disease, because the bacteria colonized the same ecological niche with the plant pathogens. This research was conducted to isolate endophytic bacteria from banana root, and study their disease suppression ability to blood disease on banana. Ninety isolates of endophytic bacteria have been isolated from the root of banana. Average population densities of bacteria varied between 6,0 x 103 and 4,2 x 105 cfu/g fresh weight of root. Twenty seven isolates positively produced inhibition zone toward blood disease bacterium. Based on plant growth and disease suppression test, ten isolates promoted the growth of banana plant and four isolates suppressed the incidence of blood disease with ranged from 66,67 to 83,33%.